Teen cyberbullying investigated : where do your rights end and consequences begin? - Jacobs, Thomas A. (Minneapolis, MN : Free Spirit Pub., 2010)
Powerful collection of landmark court cases involving teens and charges of cyberbullying, which includes: sending insulting or threatening emails, text, or instant messages directly to someone; spreading hateful comments about someone through emails, blogs, or chat rooms; stealing passwords and sending out threatening messages using a false identity; and building a Web site to target specific people. Each chapter features the seminal case and resulting decision, asks readers whether they agree with the decision, and urges them to think about how the decision affects their lives. Chapters also include related cases, important facts and statistics, and suggestions for further reading.
Part 1: Cyberbullying and the law. How did we get here? : the Internet and the First Amendment ; Ethics in an e-world ; State, Federal, and European laws on cyberbullying -- Part 2: Cyberbullying cases. Does location matter? : case: J.S. v. Bethlehem Area School District (2002) ; How a careless email can turn into a Federal case : case: Zachariah Paul v. Franklin Regional School District (2001) ; Balancing student rights and school responsibilities : case: Justin Layshock v. Hermitage School District (2007) ; Political expression or intentional harassment? : case: A.B. v. State of Indiana (2008) ; When does school discipline become unconstitutional? : case: Avery Doninger v. Lewis Mills High School (2008) ; Do libel laws apply online? : case: I.M.L. v. State of Utah (2002) ; Litigating lewdness : case: Gregory Requa v. Kent School District (2007) ; What's the issue, content or access? : case: Jon Coy v. Canton City Schools (2002) ; Free speech or true threat? : case: Joshua Mahaffey v. Waterford School District (2002) ; When creative writing becomes criminal content : case: Nick Emmett v. Kent School District (2000) ; When graphic arts get too graphic : case: Aaron Wisniewski v. Weedsport Central School District (2007) ; Prank or plan? : case: State v. Joshua Mortimer (2001) ; Know thy student handbook : case: Jack Flaherty Jr. v. Keystone Oaks School District (2003) ; Are you responsible for everything on your site? : case: Ryan Dwyer v. Oceanport School District (2005) ; So you want to be a hacker? : case: Justin Boucher v. School District of Greenfield (1998) ; When cyberbullying turns deadly : case: United States v. Lori Drew (2008) -- Closing statement -- How to do legal research -- Glossary of terms.
Includes bibliographical references and index.
Keywords: Cyberbullying -- Juvenile literature; Computer crimes -- Juvenile literature; Technology and law -- Juvenile literature; Cyberbullying; Computer crimes; Technology and law